Testing capacity of the EU banking sector to finance the transition to a sustainable economy - Slavka Eley (European Banking Authority (EBA), 2021)
Amidst increased attention on climate change, which is characterised by high uncertainties and long-term time horizons, the financial sector and supervisors are developing methods and approaches for the evaluation of climate-related financial risks. This paper proposes a transition capacity testing system based on the EU Taxonomy for environmentally sustainable economic activities as a useful tool for banks and supervisors to identify the exposures that are most vulnerable to climate change, to improve understanding of the transition financing needs and to support the greening of the financial sector.
Keywords: G21; G24; G28; G32; Q54; Q56; Q58; 330; Transition capacity testing; EU Taxonomy; climate scenario analysis; green asset ratio; transition capacitytesting ratio; ratio not likely to transition